2019
DOI: 10.1371/journal.pone.0218144
|View full text |Cite|
|
Sign up to set email alerts
|

Frequency and distribution of corneal astigmatism and keratometry features in adult life: Methodology and findings of the UK Biobank study

Abstract: PurposeTo describe corneal astigmatism in the UK Biobank population and to look for associations with other biometric variables and socio-demographic factors.MethodsThis analysis included a subsample of 107,452 participants of the UK Biobank study who underwent an enhanced ophthalmic examination including autorefractor keratometry (Tomey RC 5000, Tomey Corp., Nagoya, Japan). Participants were recruited from across the United Kingdom between 2006 and 2010, and all were between 40 to 69 years. After quality cont… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 31 publications
2
17
1
Order By: Relevance
“…22 In addition, in accordance with the impact of mean K found in our regression analysis, an increase in corneal power with increasing age could potentially also affect refractive predictability in this age group. [23][24][25] Although, this increase was not demonstrated in our patients, showing no difference in average K between groups (p=0.191), it is possible that a larger dataset, similar to these studies, is needed to exhibit this change. Interestingly, Kane et al 26 formerly evaluated the Kane formula in a specific population of patients with keratoconus.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…22 In addition, in accordance with the impact of mean K found in our regression analysis, an increase in corneal power with increasing age could potentially also affect refractive predictability in this age group. [23][24][25] Although, this increase was not demonstrated in our patients, showing no difference in average K between groups (p=0.191), it is possible that a larger dataset, similar to these studies, is needed to exhibit this change. Interestingly, Kane et al 26 formerly evaluated the Kane formula in a specific population of patients with keratoconus.…”
Section: Discussioncontrasting
confidence: 49%
“…It is therefore crucial to address this group's specific anatomical characteristics. 5,[20][21][22][23][24][25] Therefore, it would be of interest to investigate correlation of AL, keratometry and ACD with the refractive outcome in this population in a larger series of patients and to compare the elderly group to another age group. As age may represent differences in anatomical features of elderly patients, regression equation to adjust significant values may improve the predictability of the formula for this age group.…”
Section: Discussionmentioning
confidence: 99%
“…In the included studies, the following risk factors were reported to contribute to the development of astigmatism in adulthood: age, sex, race, education status, pre-existing refractive errors, and various other factors, such as urban versus rural population, degree of nuclear and cortical cataract, axial length, and presence of internal astigmatism. 31 , 35 , 41 , 43 , 46 , 47 , 50 , 51 , 53 55 , 58 , 62 64 , 66 , 71 , 79 , 81 92 …”
Section: Resultsmentioning
confidence: 99%
“…In addition, even mild keratoconus can progress in 25% of cases, 41 leading to worsening cylindrical refractive errors over time, thus affecting the validity of OCTA cross-comparisons during longitudinal follow up. Although this effect may be more significant in eyes with corneal astigmatism greater than 3.0 D, there is likely less of an effect in the general population as the average corneal astigmatism is typically around 0.50 to 1.50 D; 42,43 but caution should be noted when following quantitative OCTA metrics longitudinally as the average astigmatism may increase and change with age from WTR to against-the-rule (ATR) astigmatism. 43 Additionally, patients who have undergone surgical procedures such as cataract extraction surgery, pterygium stripping and other refractive procedures may experience a sudden and significant change in their cylindrical refractive errors, which precludes an accurate comparison of OCTA scans acquired pre-versus post-procedure.…”
Section: Discussionmentioning
confidence: 99%